EVALUASI KEBIJAKAN PUBLIK PROGRAM KELUARGA HARAPAN (PKH) DI KECAMATAN MUARA ANCALONG KABUPATEN KUTAI TIMUR - Silviani Purwanti; Raphika Buang (Jurnal Paradigma (JP), 2022)
RAPHIKA BUANG, Undergraduate Integrative Government Study Program, Faculty of Social and Political Sciences, Mulawarman University. Evaluation Of The Public Policy Of The Conditional Cash Transfer (CCT) In Muara Ancalong District, Kutai Timur Regency. The data collection technique in this study was obtained using the Purposive Sampling Technique. The data analysis used in this research is Descriptive Qualitative which aims to describe in depth the Evaluation Of The Public Policy Of The Conditional Cash Transfer (CCT) In Muara Ancalong District, Kutai Timur Regency. Intactive model data analysis from B. Miles dan a. Huberman, which begin with data reduction, data presentation, data condensation and drawing conclusion/verification. The research on Evaluation Of The Conditional Cash Transfer (CCT) In Muara Ancalong District Uses William N. Dun’s theory which includes 5 (five) evaluation indicators, Effectiveness, Efficiency, Adequacy, Equity, Responsiveness, and Accuracy. The Family Hope Program (PKH) in Muara Ancalong District has been carried out to the maximum, namely it can have a positive impact on the community, especially those belonging to the category of underprivileged communities to have a better quality of life. With the many assistance programs provided by the Family Hope Program (PKH) it helps the economy and also the community's financial independence.